The architecture of change : building a better world - Hammett, Jerilou; Wrigley, Maggie, 1958- (University of New Mexico Press, 2013)
"The anthology reprints thirty-six articles from DESIGNER/builder magazine as case studies, highlighting creative individuals and their contributions to innovative housing, neighborhood revitalization, alternative education, public art, and community empowerment through architectural design, and helping students, scholars, and community organizations understand that it is possible to integrate the principle of social justice into the built environment"--Provided by publisher.